Exploring User Experience in Virtual Industrial Heritage Platforms: Impact of Cultural Identity, Functional Clarity, Scene Interactivity, and Narrative Quality - Qi Zhou; Shuqi Wang; Jinglin Wang (Buildings)
This study aims to investigate the key factors influencing user experience in the design of virtual interactive platforms for the preservation of industrial heritage within the context of digitalization. In the literature review, this paper introduces a theoretical model comprising five latent variables: cultural identity, functional clarity, scenario interactivity, narrative quality, and user experience. To construct and validate the model, the author employed structural equation modeling (SEM) to analyze data from 323 valid questionnaires collected in China. The validation of the SEM model led to conclusions regarding the impact of each latent variable on user experience. The results indicate that cultural identity, functional clarity, scene interactivity, and narrative quality significantly affect user experience and play a critical role in enhancing user experience on virtual platforms. To validate this theoretical framework, the study employs the virtual interactive platform of Hanyang Ironworks as a case study, examining how these factors manifest in practical scenarios and their specific impact on platform design. The findings reveal that a strong sense of cultural identity, clear functional design, interactive scenes, and a well-structured narrative are the core factors that enhance user experience on virtual industrial heritage platforms. This research provides both theoretical support for the digital preservation of industrial heritage and practical insights for the design of virtual platforms. The study improves virtual interactions with industrial heritage and informs future research and applications.